Determination of official intervention: Insights from India - Rishad, Abdul; Gupta, Sanjeev; Sharma, Akhil (International Journal of Psychosocial Rehabilitation, 2020)
During the past 25 years, the Reserve Bank of India has often intervened in the foreign exchange market. The magnitude and frequency of its interventions have varied widely. This study developed a central bank reaction function that renders it feasible to examine the determinants of spot market interventions. The study employed a bivariate Probit model to examine the intervention policy of the Reserve Bank of India in the INR/U.S. Dollar market during the period from April 1995 to March 2019. The result shows that trend deviation, exchange rate volatility, market liquidity, and ‘leaning against the wind’ policy stimulate spot market purchase and sale intervention. Deviation of the trade-weighted REER stimulates spot market purchase, whereas a divergence of the export-weighted REER triggers sale intervention to maintain the equilibrium level. The study also found that accumulation of foreign exchange reserves is the by-product of intervention, not a policy outcome.